Gangguan dan Penurunan Fungsi Paru pada Pekerja Jalanan - Alvanesya Gita; Nabilla Putri Kania; Thamara Az Zahra (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Impaired and decreased lung function in street workers is still a health problem for workers in an area because air quality conditions in the work environment can have an impact on health in the workplace. Air is a sensitive environmental medium. Air pollution can be caused by natural sources or human activities. Air pollution commonly occurs in urban areas and industrial areas which produce various kinds of pollutants. The pollutants commonly found are dust, NO2, SO2, CO, and HC. Discussion: Mechanism of exposure to pollutants such as dust which causes decreased and impaired lung function, lung function disorders related to street workers, factors of decreased lung function, lung function tests, and prevention.